Two Novel Pathogenic Variants of TJP2 Gene and the Underlying Molecular Mechanisms in Progressive Familial Intrahepatic Cholestasis Type 4 Patients - Tang, Jia; Tan, Meihua; Deng, Yihui; Tang, Hui; Shi, Haihong; Li, Mingzhen; Ma, Wei; Li, Jia; Dai, Hongzheng; Li, Jianli; Zhou, Shengmei; Li, Xu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Progressive familial intrahepatic cholestasis (PFIC) is an autosomal recessive inherited disease that accounts for 10%–15% childhood cholestasis and could lead to infant disability or death. There are three well-established types of PFIC (1–3), caused by mutations in the ATP8B1, ABCB11, and ABCB4 genes. Biallelic pathogenic variants in the tight junction protein 2 gene (TJP2) were newly reported as a cause for PFIC type 4; however, only a limited number of patients and undisputable variants have been reported for TJP2, and the underlying mechanism for PFIC 4 remains poorly understood. To explore the diagnostic yield of TJP2 analysis in suspected PFIC patients negative for the PFIC1–3 mutation, we designed a multiplex polymerase chain reaction-based next-generation sequencing method to analyze TJP2 gene variants in 267 PFIC patients and identified biallelic rare variants in three patients, including three known pathogenic variants and two novel variants in three patients. By using CRISPR-cas9 technology, we demonstrated that TJP2 c.1202A > G was pathogenic at least partially by increasing the expression and nuclear localization of TJP2 protein. With the minigene assay, we showed that TJP2 c.2668-11A > G was a new pathogenic variant by inducing abnormal splicing of TJP2 gene and translation of prematurely truncated TJP2 protein. Furthermore, knockdown of TJP2 protein by siRNA technology led to inhibition of cell proliferation, induction of apoptosis, dispersed F-actin, and disordered microfilaments in LO2 and HepG2celles. Global gene expression profiling of TJP2 knockdown LO2 cells and HepG2 cells identified the dysregulated genes involved in the regulation of actin cytoskeleton. Microtubule cytoskeleton genes were significantly downregulated in TJP2 knockdown cells. The results of this study demonstrate that TJP2 c.1202A > G and TJP2 c.2668-11A > G are two novel pathogenic variants and the cytoskeleton-related functions and pathways might be potential molecular pathogenesis for PFIC.